Governance Capacity: A Critical Analysis of Vocational Education Administration Models in Local Government of Laos - Sengbandith Khinnithuck; Fang Huang; Sengbandith Phonethana (Journal of Research in Education and Pedagogy, 2026)
Centralized governance frameworks in developing economies frequently generate a fundamental tension between national policy coherence and the operational responsiveness required by diverse local labor markets. In Laos, this tension is acutely manifest within the administration of Vocational Education (VE), where provincial and district authorities bear expanding implementation responsibilities without commensurate transfers of fiscal authority, administrative capacity, or technical expertise. This study critically examines the administration models operationalized within local VE governance in Laos, identifies the structural constraints limiting their effectiveness, and proposes an evidence-grounded five-component governance reform framework. Employing a sequential explanatory mixed-methods design, the study integrates quantitative survey data from 781 stakeholders across all provinces, comprising local government officials, VE administrators, educators, and industry representatives, with semi-structured qualitative interviews and systematic policy document analysis. Quantitative findings reveal that administrative model typology (centralized, decentralized, hybrid) accounts for less than 2% of the variance in perceived governance effectiveness, whereas process-level governance qualities, institutional autonomy, stakeholder participation, decentralization depth, and resource adequacy jointly account for 56% of the variance in perceived suitability. Public-Private Partnership (PPP) strength emerges as the strongest predictor of institutional effectiveness. Qualitative findings illuminate the mechanisms underlying these patterns: local authorities function as pragmatic brokers, navigating structural rigidities through informal networks and discretionary project-based initiatives that remain institutionally unsustainable and inequitably distributed. The study identifies a centralization-responsiveness paradox wherein ceremonially adopted decentralization policies coexist with functionally centralized operations, generating accountability ambiguities and inequitable governance costs. Grounded analytically in institutional theory, decentralization theory, and human capital theory, the proposed framework integrates reconstituted multi-level governance architecture, institutionalized demand-side engagement, equitable financing, systematic capacity development, and rigorous performance accountability. Implications are discussed for policymakers, development partners, and VE administrators in comparable transitional economies.